Análisis de costo efectividad de ondansetrón para el tratamiento del vómito en niños menores de cinco años con gastroenteritis en Colombia (2015)
ABSTRACT: Introduction: Ondansetron reduces hospitalization rates for diarrhea and vomiting in children, but is not yet routinely used. Objective: To estimate from a social perspective the relative cost-effectiveness of ondansetron for the treatment of vomiting in children with gastroenteritis and at risk of dehydration in Colombia. Methods: Cost-effectiveness analysis from a social perspective, including direct medical costs and costs for caregivers. With a decision tree we compared costs and health outcomes of usual treatment without antiemetic to usual treatment plus ondansetron in children under 5 years with gastroenteritis and vomiting. Effectiveness of intervention was measured as reduction in hospitalization rates, and the time horizon of the model was the episode. Probabilities were obtained from clinical trials and systematic reviews, measurement of resources use was based on protocols and expert opinions, while unit costs were obtained from Colombian tariff manuals. We performed a survey to estimate indirect costs for caregivers (n=81) that included questions about wage loss, transportation, meals expenditures and other out-of-pocket payments. Deterministic and probabilistic sensitivity analyses were performed. Results: Usual treatment plus ondansetron is a dominant strategy compared to usual treatment without antiemetic yielding fewer hospitalizations and saving $44.562 Colombian pesos (23,98USD) per episode. Ondansetron was dominant in 98,91% of simulations of the probabilistic analysis. Conclusions: Ondansetron is a dominant intervention that reduces hospitalization rates and costs for health system and caregivers. We recommend assessing the inclusion of this drug in the Colombian Health Benefit Plan for the treatment of gastroenteritis in children under 5 years.